PENDIDIKAN KARAKTER DEWASA AWAL MEMBENTUK GENERASI YANG BERTANGGUNG JAWAB - Bansae, Munyati; Hura, Rosnila (Sekolah Tinggi Teologi Injili Abdi Allah, 2023)
Character education in early adulthood in forming a generation that is responsible and has moral integrity. This research aims to understand the impact of character education, influencing factors, character education strategies, and its benefits. In this writing there are different opinions and there are pros and cons related to the effectiveness of character education in forming a responsible generation. Some argue that character education is still relevant and important, while others doubt its effectiveness in dealing with social and cultural changes. These different opinions create the main theme of the paper, namely the role of character education in forming the character of the younger generation.The results of interviews with early adult students representing a variety of views also became an important part of the discussion, illustrating differences in viewpoints in the context of character education. While there are differences of opinion, character education in early adulthood still has an important role in forming a responsible generation. Serious efforts need to be made to integrate character education in various aspects of early adult life, including family, formal education, and the social environment. Keywords: Character Education, Early Adulthood, Generation Formation, Responsibility.